1998
DOI: 10.1074/jbc.273.20.12370
|View full text |Cite
|
Sign up to set email alerts
|

Potato Carboxypeptidase Inhibitor, a T-knot Protein, Is an Epidermal Growth Factor Antagonist That Inhibits Tumor Cell Growth

Abstract: Epidermal growth factor (EGF) and its receptor (EGFR) are involved in many aspects of the development of carcinomas, including tumor cell growth, vascularization, invasiveness, and metastasis. Because EGFR has been found to be overexpressed in many tumors of epithelial origin, it is a potential target for antitumor therapy. Here we report that potato carboxypeptidase inhibitor (PCI), a 39-amino acid protease inhibitor with three disulfide bridges, is an antagonist of human EGF. It competed with EGF for binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 42 publications
2
49
0
1
Order By: Relevance
“…methyl] thymidine incorporation below control levels, suggesting that the autocrine pathway detected may still be partly active in cells which received serum-free media every 12 hours (due to residual factors remaining after the medium change). Recently, potato carboxypeptidase inhibitor was shown to be an effective inhibitor of binding of EGF to receptors on pancreatic cancer cells but it had no effect on basal cell proliferation (Blanco-Aparicio et al, 1998). It is likely that the particular choice of cell density and medium volume in this study is responsible for the lack of effect.…”
Section: Discussionmentioning
confidence: 84%
“…methyl] thymidine incorporation below control levels, suggesting that the autocrine pathway detected may still be partly active in cells which received serum-free media every 12 hours (due to residual factors remaining after the medium change). Recently, potato carboxypeptidase inhibitor was shown to be an effective inhibitor of binding of EGF to receptors on pancreatic cancer cells but it had no effect on basal cell proliferation (Blanco-Aparicio et al, 1998). It is likely that the particular choice of cell density and medium volume in this study is responsible for the lack of effect.…”
Section: Discussionmentioning
confidence: 84%
“…Argos is expressed in response to EGF receptor activation, and is thought to contribute to receptor inhibition events critical for proper development (Stevens, 1998). Interestingly, it has been reported that potato carboxypeptidase inhibitor (CPI), a 39 amino-acid-secreted protein containing a disulphide-bonded T-knot structure moderately reminiscent of EGF-like domains, acts as an antagonist of the EGF receptor in human tumour cells (Blanco-Aparicio et al, 1998). Taken together, these observations point to the possibility that human proteins containing EGF-like domains with unusually spaced cysteine residues, or containing other disulphide-bonded structures, could act as endogenous inhibitory factors for mammalian ErbB receptor family members.…”
Section: Negative Modulator Proteinsmentioning
confidence: 99%
“…a-Chymotrypsin (EC 3.4.21.1) is a serine protease enzyme, which acts to alleviate ulcers and digesting the polypeptide of damaged tissue 10 . Recently, serine protease inhibitors from potato and other plants have also been reported to have inhibitory effects on tumor cell growth 11,12 . Such inhibitors have potential therapeutic use.…”
Section: Introductionmentioning
confidence: 99%